2006
DOI: 10.1902/jop.2006.003159
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Regenerative Potential of Guided Tissue Regeneration to Treat an Intrabony Defect and Adjacent Ridge Deformity by Orthodontic Extrusive Force

Abstract: This case report demonstrates that orthodontic-regenerative combined therapy can resolve complex clinical problems involving several dental disciplines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 14 publications
1
13
0
4
Order By: Relevance
“…Other clinical studies by Re et al [40] and Ogihara & Marks [38] revealed similar results using bovine BG. In both investigations, adult patients were recalled to a follow-up after 12 [40] or 18 [38] months. The results remained stable after those time periods.…”
Section: Reichert C Et Al Gtr Und Kfosupporting
confidence: 70%
See 3 more Smart Citations
“…Other clinical studies by Re et al [40] and Ogihara & Marks [38] revealed similar results using bovine BG. In both investigations, adult patients were recalled to a follow-up after 12 [40] or 18 [38] months. The results remained stable after those time periods.…”
Section: Reichert C Et Al Gtr Und Kfosupporting
confidence: 70%
“…Several clinical case reports [5,33,35,[37][38][39][40]48] have confirmed orthodontic tooth movement into BG reported in the animal experiments.…”
Section: Reichert C Et Al Gtr Und Kfomentioning
confidence: 72%
See 2 more Smart Citations
“…If the regenerative therapy is integrated into an ongoing orthodontic treatment, the compromised teeth should be immobilized through rigid splinting in order to stabilize the clot and the regenerative material throughout the healing phase. The regenerative therapy might follow several approaches, including open flap debridement, guided tissue regeneration (GTR) associated or not with different types of bone grafting, growth factors and more recently also stem cell-based therapy [13][14][15]. Utilization of mesenchymal stem cells in periodontal regenerative therapy has already resulted in promising outcomes that need to be further elucidated especially in terms of cell survival and efficient expression of programmed proliferative capacity to consent fully translation of mesenchymal stem cell-based therapy into clinical practice [15][16][17][18][19][20][21][22].…”
Section: Multidisciplinary Treatment Planmentioning
confidence: 99%